IMPLEMENTASI PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) UNTUK MENDORONG KEAKTIFAN BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SMP 1 MA’ARIF - Durrotun Baidok; Dina Auliya; Abd. Mukhid; Mauludatul Kamilah; Salman Abdul Karim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to understand how the implementation of learning using Information and Communication Technology (ICT) in the subject of Islamic Religious Education (IRE) and also to examine its impact on student learning activities at Ma’arif 1 Junior High School in Pamekasan. This study employs a qualitative approach and is a type of field research. Data were collected through observation, interviews, and documentation. The results indicate that instruction utilizing Information and Communication Technology (ICT) has been implemented using LCD projectors, Smart TVs, computers, laptops, the internet, instructional videos, and PowerPoint. The use of these media can enhance students’ interest, motivation, and engagement in asking questions, discussing topics, and understanding the lesson material. Supporting factors include the availability of technological facilities, teachers’ proficiency in using digital media, and student enthusiasm. Meanwhile, several obstacles exist, such as limited internet access, technical issues with devices, and variations in students’ technological proficiency. Overall, learning that incorporates ICT has a positive impact on students’ learning and makes the PAI learning process more effective and engaging.